The Effect of Contigency on Expectation of Reward in Selective Learning - Gore, Lesley (My University, 1966)
The experiment was designed to study the effect of conditionality on the growth and decline of expectancy scores during acquisition and extinction. The results revealed that conditionality affects the growth of expectation during acquisition for both direct and vicarious tasks but has no effect on variation scores. Percentage of reinforcement is also effective, the expectancy scores for the 100% reward groups rising to a higher level in acquisition and dropping off more rapidly in extinction than for the 50% reward groups. Problems arising from the differential effect of conditionality on expectancy scores and variation indices, and from differential expectancy levels at the end of acquisition were discussed.
Keywords: contingency; expectation of reward; selective learning